2005
DOI: 10.1038/sj.onc.1208856
|View full text |Cite
|
Sign up to set email alerts
|

Ets2-dependent microenvironmental support of mouse mammary tumors

Abstract: Decreasing the amount of active mouse Ets2 transcription factor by half in mice or use of a MAP kinase insensitive hypomorphic targeted Ets2 allele restricts the appearance of transgenic mammary tumors caused by either Polyoma middle T antigen (PyMT) or activated Neu/ErbB2. In addition, the early growth of transplanted mammary tumors is limited by restricted Ets2 activity of the host. Here we have tested genetically, with the use of a conditional Ets2 flox allele and tissue specific Cre recombinase expression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
5
18
0
1
Order By: Relevance
“…While mammary tumor development was not influenced by Ets2 deficiency in epithelial cells, nearly complete loss of Ets2 in the adult mouse was associated with a delay of tumor onset. As noted with constitutive Ets2 deletion, once tumors appeared, their rate of growth was not significantly altered by ubiquitious deletion [109]. These observations support the notion that stromal Ets2 expression regulates the initiation and progression of mammary epithelial tumor development.…”
Section: Ets2supporting
confidence: 75%
“…While mammary tumor development was not influenced by Ets2 deficiency in epithelial cells, nearly complete loss of Ets2 in the adult mouse was associated with a delay of tumor onset. As noted with constitutive Ets2 deletion, once tumors appeared, their rate of growth was not significantly altered by ubiquitious deletion [109]. These observations support the notion that stromal Ets2 expression regulates the initiation and progression of mammary epithelial tumor development.…”
Section: Ets2supporting
confidence: 75%
“…The im portance of the Pten-Ets2 axis in stom al fibroblasts is consistent with previous wo rk from Oshima and colleag ues that sho wed a critical cell non-autonomous role for Ets2 in m ammary tumor growth ( Tynan et al 2005). Moreover, analysis of tumor-stroma gene expression signatures identified Ets2 activation as a key event associated with breast cancer patients having the worst prognosis .…”
Section: Discussionsupporting
confidence: 75%
“…Pathological characterization showed that the absence of Ets2 in fibroblasts caused reduced epithelial tumor cell proliferation and delayed tumor progression. We also confirmed the results of Oshima's group [31], finding that deletion of Ets2 in the mammary epithelial cells had no effect on tumor growth or progression (F.L. and M.C.O., manuscript in preparation).…”
Section: The Pten/ets2 Axis In Tumor Fibroblastssupporting
confidence: 78%
“…Analysis of tumors from Ets2 A72/A72 mice suggested that lower production of extracellular matrix proteases like MMP9 correlated with lower ETS2 activity [30]. In a follow up study, this group specifically knocked out Ets2 in PyMT mammary tumor cells using a loxP conditional allele of Ets2 and MMTV-Cre, and found this deletion had no effect on tumor initiation [31]. In contrast, generalized conditional knockout of Ets2 using Mox2-Cre (MORE) also resulted in lower tumor growth.…”
Section: Ets Factors In Cancer Stromamentioning
confidence: 99%